2021
DOI: 10.1093/arclin/acaa128
|View full text |Cite
|
Sign up to set email alerts
|

Normative Reference Values, Reliability, and Item-Level Symptom Endorsement for the PROMIS® v2.0 Cognitive Function-Short Forms 4a, 6a and 8a

Abstract: Objective Reliable, valid, and precise measures of perceived cognitive functioning are useful in clinical practice and research. We present normative data, internal consistency statistics, item-level symptom endorsement, and the base rates of symptoms endorsed for the PROMIS® v2.0 Cognitive Function-Short Forms. Method The four-, six -, and eight-item short form of the PROMIS® v2.0 Cognitive Function scale assess subjective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 5 publications
1
23
0
1
Order By: Relevance
“…Regarding the CFA, the results corroborated the single-factor structure, with high factor loadings (between 0.77 and 0.92) and excellent fit indices. This was similar to the results found in a previous study, where the authors reported, in particular, a CFI = 0.995 and RMSEA = 0.050, in addition to standardized factor loadings of between 0.94 and 0.97 42 .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the CFA, the results corroborated the single-factor structure, with high factor loadings (between 0.77 and 0.92) and excellent fit indices. This was similar to the results found in a previous study, where the authors reported, in particular, a CFI = 0.995 and RMSEA = 0.050, in addition to standardized factor loadings of between 0.94 and 0.97 42 .…”
Section: Discussionsupporting
confidence: 91%
“…15 The PROMIS instruments use T score measurement, in which a score of 50 represents the mean score of a reference population (ie, the US general population), with an SD of 10. 11 , 16 For PROMIS measures, higher scores correspond to a greater degree of the outcome being measured (eg, greater fatigue). The T score was used to measure outcomes for 7 of the PROMIS-29 subscales (physical function, anxiety, depression, fatigue, social participation, 1 sleep disturbance, and pain interference) and the PROMIS SF-CF 8a survey.…”
Section: Methodsmentioning
confidence: 99%
“…En cuanto al AFC, los resultados corroboraron la estructura unifactorial, con cargas factoriales altas (entre 0.77 y 0.92) e índices de ajuste excelentes. Lo anterior fue similar a los resultados hallados en un estudio previo, donde los autores reportaron, en particular, un CFI = 0.995 y RMSEA = 0.050, además de cargas factoriales estandarizadas entre 0.94 y 0.97 42 .…”
Section: Discussionunclassified